Colon occlusion due to extraperitoneal colostomy closure - Burstin, Jacobo (Cirugía del Uruguay, 1973)
A patient underwent colostomy with extraperitoneal closure and in the immediate postoperatory period suffered intestinal invagination. The author attributes it to the reduced space left to the colon after replacing it in the abdomen.